A Comparison of Cancer Incidences Between Dharmais Cancer Hospital and GLOBOCAN 2020: A Descriptive Study of Top 10 Cancer Incidences - Bob Andinata; Adang Bachtiar; Puput Oktamianti; Jeremy Romeo Partahi; Mazaya Shafa Ainan Dini (Indonesian Journal of Cancer, 2023)
Background: : Cancer is one of the main causes of death and increased morbidity in every country in the world. According to Global Cancer Observatory (GLOBOCAN) 2020 data, it is estimated that 19.3 million new cancer cases and nearly 10.0 million cancer deaths occurred in the world in 2020. Based on the same data, it is estimated that 396,914 new cancer cases and nearly 234,511 cancer deaths are estimated to occur in Indonesia. Dharmais National Cancer Hospital (DNCH) as a national cancer center is a miniature of cancer data in Indonesia. For this reason, researchers want to compare whether the data on the number and types of cancer in DNCH are the same as those in GLOBOCAN 2020.Methods: This research is a descriptive analysis with secondary data collection methods taken from medical records. The sampling technique was total sampling, univariate data analysis, namely new cases of cancer patients for the January-December 2021 period which are 2,382 cases.Results: The results showed that the same order in both data was only found in the first, second, and seventh order, namely breast cancer, cervical cancer, and non-Hodgkin’s lymphoma, respectively. However, the percentage of new cases of breast cancer in RSKD is much higher (2.5-folds) than in GLOBOCAN.Conclusion: There are several differences between the data on new cancer cases in the two data, which can be caused because DNCH has complete facilities, both for diagnostic and curative purposes, and examinations such as IHC and bone scans are only available at certain hospitals and one of them is DNCH.